Some central effects of 5-hydroxytryptamine in young chickens at and below thermoneutrality. - Marley, E (1975)
1 Three salts of 5-hydroxytryptamine, the hydrogen maleinate, the oxalate and the creatinine sulphate were infused into the hypothalamus of 10-18 day old chickens at ambient temperatures in and below the thermoneutral range. Body temperature was recorded and behaviour observed. Electrocortigrams were recorded in experiments in which 5-hydroxytryptamine hydrogen maleinate was used. The effects of a monoamine oxidase inhibitor and methysergide on these responses were similarly studied. 2 At thermoneutrality (31 degrees C) all 3 salts produced behavioural sleep. 5-Hydroxytryptamine oxalate had inconsistent effects on body temperature. 5-Hydroxytryptamine creatinine sulphate produced hypothermia at small doses and mild hyperthermia at higher doses. 5-Hydroxytryptamine hydrogen maleinate produced hypothermia at all doses tested; the falls in temperature induced by this salt were intensified in magnitude and duration by monoamine oxidase inhibition unlike the responses to the other 2 salts. 3 At temperatures below thermoneutrality (16 degrees C) all 3 salts produced behavioural sleep and electrocortical sleep was recorded with 5-hydroxytryptamine hydrogen maleinate. All 3 salts produced hypothermia, which was intensified in magnitude and duration by monoamine oxidase inhibition. 4 The hypothermia produced by 5-hydroxytryptamine hydrogen maleinate was prevented by equimolar doses of methysergide. 5 The position of the cannula in the hypothalamus was found to be crucial. 6 The results contrast with those found in the adult fowl. No conclusion is drawn as to the relationships of the actions of these salts when infused compared with the effects of endogenous 5-hydroxytryptamine release.